Load balancing with shadowing effects handover in Li-Fi and RF hybrid network - Al-Bayati, Sallar Salam Murad (2018)
Light Fidelity (LiFi) uses light emitting diodes (LEOs) for high speed wireless communications. a hybrid network combining light fidelity (Li-Fi) with a radio frequency (RF) wireless fidelity (Wi-Fi) network is considered. An additional tier of very small Li-Fi attocells which utilise the visible light spectrum offers a significant increase in wireless data throughput in an indoor environment while at the same time providing room illumination. Importantly, there is no interference between Li-Fi and Wi-Fi. A Li-Fi attocell covers a significantly smaller area than a Wi- Fi access point (AP). This means that even with moderate user movement a large number of handover between Li-Fi attocells can occur, and this compromises the system throughput. Dynamic load balancing (LB) can mitigate this issue so that quasi-static users are served by Li-Fi attocells while moving users are served by a Wi-Fi AP. However, due to user movement, local overload situations may occur which prevent handover, leading to a lower throughput. LiFi can significantly alleviate the traffic bottlenecks in high density RF scenarios, typically present in an indoor environment. Hence, a combination of LiFi and RF networks becomes a promising candidate for future indoor wireless communications. In a practical indoor scenario, the optical interference from neighbouring LiFi access points (APs) and the blockages of line-of-sight (LoS) optical channels induced by people and objects are the main factors that cause significant optical channel variations. This research studies LB in a hybrid Li-Fi/Wi-Fi network by taking into account user mobility and handover signalling overheadsl, and also Inthis study, the effect of these two factors on the system throughput of a hybrid LiFilRF network is investigated. Furthermore, a dynamic LB scheme is proposed, where the utility function considers system throughput and fairness. In order to better understand the hand over effect on the LB, the service areas of different APs are studied, and the throughput of each AP by employing the proposed LB scheme is analysed. In order to offer a fair comparison, area data rate, which is defined as the system throughput in a unit area, is used for performance evaluation. The simulation shows that there is an optimal distance between two neighbouring LiFi APs to achieve the highest area data rate. In addition, the area data rate increases with the density of blockages when the blockage density is below a certain threshold.